Я - судья. Кредит доверчивости: [роман] / Татьяна Устинова, Павел Астахов - Устинова Татьяна Витальевна (Я - судья, 2012)
Экземпляры: Ф. 2 (20200114) / Инвентарный номер: 47510 / Цена: 40.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: У 80 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44